Early Effects of Repetitive Transcranial Magnetic Stimulation Combined With Sertraline in Adolescents With First-Episode Major Depressive Disorder - Chen, Haisi; Hu, Xiwen; Gao, Jingfang; Han, Huan; Wang, Xiaole; Xue, Chuang (Frontiers in Psychiatry, 2022)
Background Adolescence is a period of high incidence for depression. However, there is a limited treatment option for the adolescent depression. For treatment-resistant major depressive disorder, HF-rTMS of the left dorsolateral prefrontal cortex (DLPFC) appears therapeutically effective. The aim of the study is to explore the early effects of repetitive transcranial magnetic stimulation in combination with sertraline in adolescents with first-episode major depressive disorder. Methods A total of 100 teenage patients with first-episode depression were randomly divided into the study groups. Both groups were treated with sertraline. In addition, the study group was treated with ten sessions of add-on rTMS. The control group was given sertraline only. The depressive symptom and cognitive function were assessed by the Hamilton depression rating scale 17 version (HAMD-17), Children’s Depression Rating Scale-Revised (CDRS-R), Integrated visual and auditory continuous performance test (IVA-CPT), and THINC-it. Results The number of early improvers after 2 weeks of treatment in the study group was statistically significant higher compared to the control group (95.83% vs 73.47%, χ2 = 9.277, P = 0.002). There was significant difference observed in responder rates (62.50% vs. 28.57%, χ2 = 11.262, P = 0.001) or in remission rates (31.25% vs. 6.12%, χ2 = 10.130, P = 0.001) between the two groups at 4 weeks. The score of HAMD-17 and CDRS-R in the study group were significantly lower than the control group (Fgroup = 12.91 vs 10.21, P < 0.05). Attention Quotient (listening, visual and full-scale) attention quotient of IVA-CPT in the study group were higher than those in the control group after treatment, and the differences were statistically significant(P < 0.05). The study group showed higher score in Spotter than the control group after treatment (P < 0.05). Discussion This is the most extensive blinded, randomized clinical study to date examining the efficacy of 10-Hz add-on rTMS for first-onset adolescent depression. Our results support that add-on rTMS accelerates the efficacy of the antidepressants, improving the depressive symptoms and cold cognitive function in first-episode adolescent depression. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [ChiCTR2100048534].